Physicians' Perception of Sickle-cell Disease Pain - Lucchesi, Fatima; Figueiredo, Maria Stella; Mastandrea, Erika B.; Levenson, James L.; Smith, Wally R.; Jacinto, Alessandro F. [UNESP]; Citero, Vanessa de A. (Natl Med Assoc, 2016)
The aim of this study was to evaluate the physician's perception of pain experienced by patients with sickle-cell disease (SCD). Pain experiences reported by patients were compared with physicians' perception of the patient's pain, and the treatment decision-making process was evaluated. Fifty-two patient-physician pairs were assessed. Before the clinic visit, the patients completed a 3-item on pain experienced 24 h prior to the visit and the PHQ-9. After the patient visit, the physicians completed a questionnaire assessing their perception of the patient's pain and a questionnaire on the factors taken into consideration when evaluating the patient's pain experience. The physicians rated the patients' pain as more intense than did the patients themselves; and there was agreement between pain intensity measurements (p < 0.05). The physicians' perception was influenced by the pain intensity reported by the patient, results of blood count at the time of the patient visit, and medication availability in the public health services. However, these factors were not predictive of the patient's pain intensity perceived by the physician. Patients' depressive symptoms were not predictive factor of the physicians' perception. Biochemical, genetic and symptomatic characteristics of SCD influenced the physicians' perception of the patient's pain experience, while psychosocial aspects did not.
Keywords: Sickle; cell; Pain perception; Physician-patient relations; Attitude of health personnel